2016
DOI: 10.17577/ijertv5is050181
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Rheological Behaviour and Heat Transfer Performance of Alumina Nanofluid

Abstract: In this work, Al 2 O 3 Nanoparticles with mean diameter of 25nm, surface area 180m 2 /g dispersed in base fluid using two step method with the nanoparticles volume concentrations 0.1%, 0.2%, 0.3%, 0.4% and 0.5% using magnetic stirrer and sonicator. Two different base fluids were used, Distilled Water (DW) and Distilled Water:Ethylene Glycol (EG) mixture (70:30%, 80:20% & 90:10%). 40 samples were prepared with the four base fluids with and without capping agent (Cetyltrimethyl Ammonium Bromide-CTAB). First part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…into the boundary layer region) whereas the opposite behaviour is noticed for temperature gradients associated with the Nusselt number. However as with the skin friction, there is a depletion in the nano-particle concentration gradient with progress into the boundary layer transverse to the wall and this verifies the earlier results described relating to greater Sherwood numbers always being computed at the wall, associated with the agglomeration of nano-particles (although the effect is somewhat weaker for pseudo-plastic nanofluids compared with dilatant nanofluids, as noted in [22,52,53]).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…into the boundary layer region) whereas the opposite behaviour is noticed for temperature gradients associated with the Nusselt number. However as with the skin friction, there is a depletion in the nano-particle concentration gradient with progress into the boundary layer transverse to the wall and this verifies the earlier results described relating to greater Sherwood numbers always being computed at the wall, associated with the agglomeration of nano-particles (although the effect is somewhat weaker for pseudo-plastic nanofluids compared with dilatant nanofluids, as noted in [22,52,53]).…”
Section: Resultssupporting
confidence: 82%
“…achieve enhanced heat transfer rates at the wall and this has also been corroborated by experiments reported in Raghulnath et al[52] and Akhavan-Behabadi et al[53] for metallic nanofluids. This is surmised to be a result of larger concentrations of nano-particles associated with smaller sized-nanoparticles (higher Brownian motion number).…”
supporting
confidence: 78%
“…A foretaste of nanofluidic thermal conductivity can be seen in reviews by Murshed et al [13], Das and Choi [14]. Another thermophysical property viscosity has also attracted the researchers [7,[15][16][17].It is seen from these investigations and reviews that the viscosity increases with increase in concentration of nanofluids and decreases with decrease with increase in temperature as concluded by Saini et al [3] in his review. So this was the one of the method enlisted above to increase the heat dissipation from the small spaces.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the better thermophysical properties of nanofluids they are preferred over the base fluids. Thermal conductivity is the most studied property of nanofluids as can be seen from the available literature [5][6][7][8][9][10][11][12]. From the literature available it can be concluded that thermal conductivity of nanofluids increases with increase in concentration of nanoparticles in base fluids, also the thermal conductivity increases with increase in temperature.…”
Section: Introductionmentioning
confidence: 99%